2018
DOI: 10.1080/10641963.2018.1469644
|View full text |Cite
|
Sign up to set email alerts
|

Association of the placental VEGF promoter polymorphisms and VEGF mRNA expression with preeclampsia

Abstract: The current study found higher mRNA expression of placental VEGF gene in PE women. The mRNA expression of the placental VEGF gene has been up-regulated in the placenta of women with -634CC genotype. No association was found between the placental VEGF -1154G/A and -2549 I/D polymorphisms and VEGF mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Keshavarzi et al [ 16 ] found higher placental VEGF gene mRNA expression in PE women with the-634CC genotype. However, the study showed the mRNA expression of the placental VEGF gene has been up-regulated in the placenta of women with -634CC genotype but no association between VEGF mRNA expression and the placental VEGF -1154G/A and -2549 I/D polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keshavarzi et al [ 16 ] found higher placental VEGF gene mRNA expression in PE women with the-634CC genotype. However, the study showed the mRNA expression of the placental VEGF gene has been up-regulated in the placenta of women with -634CC genotype but no association between VEGF mRNA expression and the placental VEGF -1154G/A and -2549 I/D polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported investigation of VEGF genetic polymorphisms in the neonatal period, with four studies completed in the fetal period [ 15 , 16 , 17 , 18 ]. The evaluated articles included three meta-analyses [ 19 , 20 , 21 ], six reviews [ 15 , 22 , 23 , 24 , 25 , 26 ], and one clinical trial [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…28 2.2.1 | VEGF gene VEGF is a growth and hypoxia-induced factor involved in the regulation of proliferation, vascular permeability, function, and differentiation of endothelial cells. 29 VEGF signaling can stimulate endothelial no-synthase (eNOS) and increase the production of potent vasodilator nitric oxide (NO). 30 Therefore, the expression pattern of VEGF is closely related to the occurrence of PIH.…”
Section: Genetic Polymorphisms In the Endothelin Systemmentioning
confidence: 99%
“…The maternal genotype was significantly correlated with PE risk (P=0.028). 95% CI: (0.40-3.18; 0.11-1.10) of GC and CC genotypes shows this factor is not associated with PE; whether there is an association between their geneenvironment interactions should be further investigated (25)(26)(27). In the RMDR interaction model study (28), the -1562CT genotype with VEGF-634CC, -634GG, and matrix metalloproteinase-9 genes are more common in the PE group than in the normal pregnancy group.…”
Section: Locus-634g/c and Pementioning
confidence: 99%